2022
DOI: 10.3390/ijerph191610418
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen Profile of Children Hospitalised with Severe Acute Respiratory Infections during COVID-19 Pandemic in the Free State Province, South Africa

Abstract: Severe acute respiratory infections (SARI) contribute to mortality in children ≤5 years. Their microbiological aetiologies are often unknown and may be exacerbated in light of coronavirus disease 19 (COVID-19). This study reports on respiratory pathogens in children ≤5 years (n = 84) admitted with SARI during and between the second and third waves of COVID-19 infection in South Africa. Nasopharyngeal/oropharyngeal swabs collected were subjected to viral detection using QIAstat-Dx® Respiratory SARS-CoV-2 Panel.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 87 publications
(121 reference statements)
6
17
1
1
Order By: Relevance
“…However, both studies highlighted the several advantages of mNGS over the mRT-PCR and suggested that lower abundance of the viruses detected by RT-PCR could have resulted in a lower detection rate by mNGS. Furthermore, corresponding with the previously reported data from the mRT-PCR assay in the same patients, 25 RSV and HRV were the most predominant viral pathogens detected in the respiratory samples by the mNGS-based approach. This observation agrees with others who showed that RSV and HRV are the most prevalent viruses in children with SARI.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…However, both studies highlighted the several advantages of mNGS over the mRT-PCR and suggested that lower abundance of the viruses detected by RT-PCR could have resulted in a lower detection rate by mNGS. Furthermore, corresponding with the previously reported data from the mRT-PCR assay in the same patients, 25 RSV and HRV were the most predominant viral pathogens detected in the respiratory samples by the mNGS-based approach. This observation agrees with others who showed that RSV and HRV are the most prevalent viruses in children with SARI.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, corresponding with the previously reported data from the mRT‐PCR assay in the same patients, 25 RSV and HRV were the most predominant viral pathogens detected in the respiratory samples by the mNGS‐based approach. This observation agrees with others who showed that RSV and HRV are the most prevalent viruses in children with SARI 4,8,45,46 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is due to the overall decrease in bacterial respiratory infections due to NPIs. The positive rate of viral infection in ARI patients aged <5 years increased after COVID-19, as was also seen in South Africa, where NPIs during COVID-19 changed the infection spectrum, making children more likely to be infected with other respiratory viruses [27]. The proportion of ARI patients with clinical symptoms decreased after COVID-19, which may be related to the decreased positive rates of viral and bacterial infections after COVID-19.…”
Section: Discussionmentioning
confidence: 59%